1995
DOI: 10.1001/archinte.1995.00430150057006
|View full text |Cite
|
Sign up to set email alerts
|

Health-Care Expenditures for Tuberculosis in the United States

Abstract: Treatment accounted for more than 86% of all TB-related expenditures; inpatient treatment accounted for 60% of the total. Prevention activities made up only 14% of all costs. Direct medical expenditures may be underestimated because of limitations in the database on hospital expenditures and health department cost-accounting systems and because of the lack of a national database on screening activities. Greater emphasis should be placed on outpatient treatment and prevention in high-risk populations, and impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(20 citation statements)
references
References 22 publications
2
16
1
1
Order By: Relevance
“…Hospitalization frequencies and LOS in our study were comparable to other US and Canadian studies [12, 14, 21]. In the one US study to differentiate initial and during-treatment hospitalizations, Taylor found that 45% of TB patients had an initial hospitalization for TB and 8% were hospitalized during treatment, with a median LOS of 11 days [14].…”
Section: Discussionsupporting
confidence: 85%
“…Hospitalization frequencies and LOS in our study were comparable to other US and Canadian studies [12, 14, 21]. In the one US study to differentiate initial and during-treatment hospitalizations, Taylor found that 45% of TB patients had an initial hospitalization for TB and 8% were hospitalized during treatment, with a median LOS of 11 days [14].…”
Section: Discussionsupporting
confidence: 85%
“…Our estimated cost of investigating a contact ($250) is slightly lower than other estimates (~$300) 23,24. If the investigation costs are higher than our estimated costs, the CPM would be even more cost-effective.…”
Section: Discussioncontrasting
confidence: 54%
“…A full course (6 months) and a partial course of INH treatment were estimated to cost $13.80 and $6.90, respectively. The treatment of active TB disease was estimated to cost $12 160, which represented a weighted average of inpatient ($14 777) and outpatient ($4 774) costs 13,20,23–25…”
Section: Methodsmentioning
confidence: 99%
“…In 1991 dollars, the initial hospitalization for these patients is estimated to have cost у$18,588/hospitalization. The total-cost estimate, $3.0 million, is likely an underestimate, since the median duration of hospitalization for the study patients was 34 days, compared with the 20 days reported by Brown et al [22]. In addition, during the course of TB treatment, there were an additional 207 hospitalizations comprising 8627 days.…”
Section: Discussionmentioning
confidence: 99%